Review of computerized cognitive behavioural therapy based on culture centered design for substance abuse in Malaysia - Zainul Akramin Mohd Drus,; Dalbir Singh,; Mohd Rosmadi Mokhtar,; Rusdi Abd Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Addiction is an activity that includes video games, internet, gambling and substance abuse such as drugs, cigarettes and alcohol. These symptoms had spread among adults, adolescents and children. The phenomenon could be resolved through various approaches in the area physiological therapies such as Cognitive Behavioural Therapy (CBT). CBT plays a vital role, whereby it is a face-to-face therapy between patient and counsellor that treats emotional and physical health conditions. The advancement of information technology has spawned new innovations for therapy using computer known as Computerized Cognitive Behavioural Therapy (CCBT). The central issue concerning CCBT focuses on the patient’s continuous engagement throughout entire therapy. It is known that continuous engagement in using CCBT is dependable on the patient’s cultural background. Indirectly, it proves the existence of factors that influence patient’s preferences and engagement towards CCBT. Therefore, designing appropriate design interface based on Culture Centred Design (CCD) in order for patient to sustain their engagement level towards CCBT is essential. Furthermore, patients also fail to complete the therapy due to the lack of interest and focus, resulting in disengagement towards CCBT. Various engagement models and theories on developing cultural based interface for CCBT was discussed. Therefore, research aims to review literatures, identify factors that prone to provide continuous engagement CCBT interface which would trigger and guide future research works.